2020
DOI: 10.26754/ojs_ried/ijds.431
|View full text |Cite
|
Sign up to set email alerts
|

La sociedad civil y la Agenda 2030. Una evaluación de la implementación de las acciones de los ODS en el Distrito Metropolitano de Quito

Abstract: La coordinación entre múltiples centros para la toma de decisiones y los tipos de actores, en todas las escalas y sectores, resulta fundamental para mejorar la efectividad de la implementación de la Agenda 2030 y los objetivos de desarrollo sostenible (ODS). Tal desafío es especialmente crucial para los acuerdos metropolitanos en los países en desarrollo donde la capacidad del Estado se muestra débil y las personas, a menudo, carecen de recursos para actuar sobre los problemas a los que deben enfrentarse. En e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Despite the long-term interest in investigating environmental decentralization at the local level, empirical studies on how local governance conditions affect the political priority received by different SDGs are only emerging (see Cisneros, Cabrera-Barona and López 2020). Our research continues this line of work, highlighting the role of institutions in tackling environmental issues through local interventions in Ecuador.…”
Section: Introductionmentioning
confidence: 71%
“…Despite the long-term interest in investigating environmental decentralization at the local level, empirical studies on how local governance conditions affect the political priority received by different SDGs are only emerging (see Cisneros, Cabrera-Barona and López 2020). Our research continues this line of work, highlighting the role of institutions in tackling environmental issues through local interventions in Ecuador.…”
Section: Introductionmentioning
confidence: 71%
“…A eficiência de um SAS está intimamente ligada à qualidade da interação entre esses grupos. A coordenação entre múltiplos setores de tomada de decisão e tipos de atores é essencial para o alcance das metas dos ODS, principalmente nos grandes centros urbanos ( 14 ).…”
Section: Resultsunclassified
“…Furthermore, the lack of police protection can promote informal social organization to face crime [4]. In rural parishes of the MDQ, informal networks of governance operate, for instance, Cisneros et al [56] identified complex networks of collaboration between a diversity of actors in rural parishes of the MDQ.…”
Section: Discussionmentioning
confidence: 99%